CHARACTER EDUCATION BASED ON THE SPIRITUAL EXPERIENCES OF MATAN MEMBERS - Faizah, Latifatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze character education based on the spiritual experiences of MATAN members. This research also aims to teach character habituation through spiritual activities, MATAN (Mahasiswa Ahli at Thoriqoh Al Mu'tabaroh An Nahdliyah) also provides lessons about the journey and struggle of Sufi figures who always connect their worldly life with the afterlife delivered by a murshid (teacher). This research method uses a descriptive qualitative research approach with a case study type of research at Nurul Jadid Paiton Probolinggo. Data collection tools in this study used observation and in-depth interviews to support the completeness of the data. The data analysis technique in this study was carried out with the stages of data collection, reduction, and conclusion of research results. From this study, it was found that the cultivation and application of character education is very effective within the scope of the pesantren. With several methods, namely the method of example, habit, advice, and story. This research shows that Islamic values are a full support in the successful implementation of character education with complete pesantren components, of course with consistent effort and full discipline